2020
DOI: 10.1017/s0956536119000075
|View full text |Cite
|
Sign up to set email alerts
|

Point Counter Point: Interpreting Chipped Chert Bifaces in Terminal Classic “Problematic” on-Floor Deposits From Structures A2 and A3 at Cahal Pech, Belize

Abstract: Problematic deposits, containing different types of artifacts and skeletal remains, are typically recovered on or near the surfaces of the terminal phase of elite civic-ceremonial architecture at ancient Maya sites. These contexts often date to the Terminal Classic period (~a.d. 750–900). They have been variously interpreted as evidence for site abandonment, squatting, warfare, or dedication or termination rituals. Sixteen chert bifaces were recovered from problematic deposits at the bases of Structures A2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Their deposition within the cenote, however, forces us to consider alternative functions for their final use. In the case of the cenote assemblage, that function is most likely ritual in nature, a situation similar to that noted by Awe and Helmke (2015, 2019) for a European sword deposited by the Maya in Rapier Cave in Western Belize, and by Stemp and Awe (2020) for the chert projectile points from the peri-abandonment deposits at Cahal Pech.…”
Section: Comparisons To Cultural Remains Recovered From the “Cenote Osupporting
confidence: 64%
See 2 more Smart Citations
“…Their deposition within the cenote, however, forces us to consider alternative functions for their final use. In the case of the cenote assemblage, that function is most likely ritual in nature, a situation similar to that noted by Awe and Helmke (2015, 2019) for a European sword deposited by the Maya in Rapier Cave in Western Belize, and by Stemp and Awe (2020) for the chert projectile points from the peri-abandonment deposits at Cahal Pech.…”
Section: Comparisons To Cultural Remains Recovered From the “Cenote Osupporting
confidence: 64%
“…Instead, based on the multiple lines of evidence we describe above, we suggest that these cultural remains were deposited at sites across the region by remnant populations still living at these centers (Lamoureux-St-Hilaire et al 2015), or by local communities who conducted pilgrimages and/or propitiation rituals at the sacred places of their ancestors. That those involved are likely local is suggested by the strontium isotope analysis of the human remains we have recovered in both intrusive burials and deposits at the sites, and by the fact that the deposits mostly contain locally produced objects (Aimers and Awe 2020; Stemp and Awe 2020). This perspective also fits the general consensus that abandonment of Maya sites was not an overnight phenomenon, but rather a gradual, perhaps even protracted, process that took place over several years (Webster 2002).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The contextual distribution of the 23 complete bifaces was particularly interesting as seven of them were found close together on the north flank of the Structure A2 stairside outset, nine were scattered in the northeast corner of Plaza A, and the other seven were to the west of the Structure A3 stairside outset. In their study of the bifaces, Stemp and Awe (2020) observed that the contextual and numerical distribution of the bifaces are ideologically significant because the numbers seven and nine are often associated with celestial and underworld realms in Maya cosmology (Miller and Taube 1993:151–152). We should also note that usewear analysis of the bifaces is consistent with use as projectiles.…”
Section: The Spatial Context Of Peri-abandonment Deposits At Cahal Pechmentioning
confidence: 99%
“…a.d. 750–900) period. Other papers in this special issue of the journal provide detailed discussions of the ceramic (Aimers and Awe 2020) and chert (Stemp and Awe 2020) artifacts in the peri-abandonment deposits at Cahal Pech and on the results of our investigations of similar deposits at Baking Pot (Hoggarth et al 2020) and at Xunantunich, Altun Ha, Caracol, and Pook's Hill (Awe et al 2020).
Figure 1.Map of Western Belize, indicating location of sites discussed in text.
…”
Section: Introductionmentioning
confidence: 98%